2005
DOI: 10.1099/mic.0.27938-0
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression profile of mycobacterial surface glycopeptidolipids following treatment with the antifungal azole inhibitors econazole and clotrimazole

Abstract: The azole antifungal drugs econazole and clotrimazole are known cytochrome P450 enzyme inhibitors. This study shows that these drugs are potent inhibitors of mycobacterial growth and are more effective against Mycobacterium smegmatis than isoniazid and ethionamide, two established anti-mycobacterial drugs. Several non-tuberculous mycobacteria, including the pathogenic members of the Mycobacterium avium-intracellulare complex (MAC) and the fast-growing saprophytic organism M. smegmatis, produce an array of sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…In M. smegmatis, econazole and clotrimazole inhibited synthesis of glycopeptidolipids, a major component of the bacterial outer layer (40). Although CYP121 is refractory to optical change upon interaction with a variety of lipids and steroids, we have been able to demonstrate binding interactions between CYP121 and crudely fractionated lipids from Mtb (ongoing studies).…”
Section: Determination Of Mic Values For Azole Drugs Against M Tubermentioning
confidence: 89%
“…In M. smegmatis, econazole and clotrimazole inhibited synthesis of glycopeptidolipids, a major component of the bacterial outer layer (40). Although CYP121 is refractory to optical change upon interaction with a variety of lipids and steroids, we have been able to demonstrate binding interactions between CYP121 and crudely fractionated lipids from Mtb (ongoing studies).…”
Section: Determination Of Mic Values For Azole Drugs Against M Tubermentioning
confidence: 89%
“…A number of these compounds, e.g., calcimycin, demeclocycline, doxycycline, lomefloxacin, minocycline, ofloxacin, and vancomycin, are known antibacterials, and therefore, activity against mycobacteria was not unexpected. In (6,22). From our review of the literature, antimycobacterial activity has not been previously reported for the remaining compounds, calmidazolium, diphenyleneiodonium, idarubicin, and methoctramine.…”
mentioning
confidence: 89%
“…Econazole was found to be bactericidal for M. smegmatis grown in culture. Additionally, a recent study showed that the biosynthesis of M. smegmatis glycopeptidolipids is inhibited with econazole and clotrimazole treatment, and that both azoles inhibited M. smegmatis growth with MIC values of 2 and 0.5 g/ml, respectively; the authors speculate that inhibition of the CYP51 from M. smegmatis is involved in the biosynthesis of glycopeptidolipids (42).…”
Section: Discussionmentioning
confidence: 99%